Kuchala (Strychnous Nuxvomica Linn) - Known as Toxic and Less Known as an Effective Medicinal Herb (AYUSHDHARA, 2021)
Strychnous nuxvomica Linn, known as Kuchala in Ayurveda is a well known poisonous herb that consists of multiple health benefits in Indian system of medicine. In Ayurveda, it is said as Upavisha and used as a popular folk medicine from ancient times. This Kuchala is still being used in rural India in the medicinal form. Strychnine is a main contain of Kuchala which was first used in 1540 for the purpose of medicine and continued to be used in many stimulants, tonics and cathartics. It includes constituents like alkaloids with flavonoids, iridoids and phenolic glycosides. Research studies have reported its anti-allergic, anti-inflammatory, antimicrobial, anticancer, antipyretic, gastroprotective, antidiabetic, antialcoholic, hepatoprotective, antioxidant, antinociceptive, anti-snake venom and neuropharmacological properties. Though considered as an extremely poisonous plant, but has enormous medicinal properties.